Issue Notes - , Editor (Historical Papers, 2022)
The papers presented by Daniel Goodwin (“The Founding Vision of the Canadian Council of Churches”), Dennis R. Hoover (“The Politics of Conservative Protestant – Conservative Catholic Alliances in the United States and Canada”), Samuel Reimer (“The Ecumenical Impulse Among Canadians”), Bruce L. Guenther (“Slithering Down the Plank of Intellectualism? The Canadian Conference of Christian Educators and the Impulse Towards Accreditation Among Canadian Bible Schools During the 1960s”); Timothy E. Strauch (“The Jubilee Riots, the Orange Order and the Preservation of Protestantism in Toronto, 1875”), Colleen Gray (“Eighteenth-Century Clerical Biography and Narrative Technique in Imaging Sainthood: Two Biographers of Marie Barbier”), Douglas H. Shantz (“Pietists Representations of Sixteenth Century Radicals as found in the Works by Gottfried Arnold and Johann Heinrich Reitz”), Thomas Evans (“The ‘Englishness’ of John Medley, First Bishop of Fredericton, 1845-1892”), Russel Prime (“Trains, Boats and Magistrates: Disciples’ Evangelists Proclaiming the Gospel in the Maritimes, 1883-1903”), James Opp (“Re-imaging the Moral Order of Urban Space: Religion, Photography and the City”), Marguerite Van Die (“It Takes a Village: Evangelical Childhood Nurture and Moral Formation in Stanstead, Quebec, 1830-1880”), and Lynne Marks (“A God-Fearing Nation? Church Involvement Across Canada in 1901”) were not made available for publication.